Application of European approaches to the determination of technological indicators of the best available techniques in the field of wastewater treatment - Oleg V. Grevtsov; Maksim E. Astrakhanov; Andrey N. Epov (Водное хозяйство России: проблемы, технологии, управление)
The year 2014 was a turning point in the transition of the main sectors of the Russian economy to a new track of environmental regulation and the introduction of obligations for first category’ s objects of negative environmental impact to receive a unified complex document containing mandatory requirements in the field of environmental protection. The main element in the application for a comprehensive environmental permit is the results of calculations of technological standards based on technological indicators of the best available techniques.The determination of technological indicators of the best available techniques takes place in the process of developing and updating information and technical reference documents (BREFs) on the best available techniques. There is currently no unified methodology for determining the technological indicators of the best available techniques. In the process of determining them in Russia, an expert assessment, a reference to the opinion of the industry professional community, or a compromise between control and supervisory authorities, departmental executive authorities and enterprises prevails.